Richer and cleaner - at others' expense? - Taran Fæhn; Annegrete Bruvoll (Statistics Norway, Research Department, 2006)
Pollution intensive production can be avoided domestically by increased imports and less exports of dirty products. Such trade effects may imply more emissions abroad, or pollution leakages. We study whether such leakages may contribute to the observed inverted relationship between emissions and economic growth - the Environmental Kuznets Curve (EKC). In our case, the rich, open Norwegian economy, we find little evidence for the hypothesis that pollution leakages contribute to explain the EKC. Despite an observed decoupling of emissions from economic growth over the past 20 years, there was no increase in pollution leakages over this period. Rather, emissions related to export increased far more than the foreign emissions embodied in import, implying reduced leakages. In future projections, we find a lower degree of decoupling than in the past, but no corresponding reductions in leakages. Instead, leakages increase. This conclusion is fairly invariant to assumptions about future climate policy.
Keywords: D58; O11; Q25; Q28; Q48; 330; Climate policy; dynamic CGE model; endogenous policy; Environmental Kuznets Curve; pollution leakage